LIFESTYLE DAN WORD OF MOUTH DALAM MEMBENTUK MINAT BELI ULANG DALAM PENGGUNAAN E-WALLET DANA PADA BISNIS MAKANAN DAN MINUMAN DI TOKO MIXUE SITUBONDO DENGAN KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING - Maffiro, Dhella Monica Ayu; Hamdun, Edy Kusnadi; Fandiyanto, Randika (Fakultas Ekonomi dan Bisnis, 2023)
There is a change in people's habits in the transaction process from using cash to using cashless. One cashless payment that is widely used by consumers of Mixue Situbondo is E-Wallet DANA. E-Wallet DANA is a widely used payment application because of its practicality, easiness, safety, and many discounts offered. This research aims to determine how lifestyle and word of mouth influence repurchase interest with purchase decision as an intervening variable. This quantitative research used 27,000 consumers of Mixue Situbondo Stores as the population. The sampling technique used was purposive sampling and produced a sample of 100 respondents. The primary data of this research were obtained by distributing questionnaires via barcodes at the Mixue Situbondo. Then the data were processed using the Smart PLS 3.0 program. The results of this study indicate that lifestyle has an effect positive significant effect on purchasing decisions, word of mouth gives a positive significant effect on purchasing decisions, lifestyle has a significant effect positive on repurchase intention, word of mouth has a significant positive effect on repurchase intention, purchase decision has a positive effect but not significant to repurchase intention, and lifestyle has a positive effect but not significant to repurchase intention through purchase decision as an intervening variable. Word of mouth has a positive but not significant effect on repurchase intention through purchasing decisions as an intervening variable.